Implementasi Manajemen Pembelajaran Daring pada Masa Pandemi COVID 19 di SMP Negeri 7 Sijunjung - Rika Wahyuni; Suswati Hendriani; Devy Aisyah (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2021)
The sudden spread of the covid-19 virus has resulted in social changes that have caused stuttering in the process of adjusting learning activities. That's why online learning must be done in order to achieve ideal learning at SMP Negeri 7 Sijunjung. This study aims to describe the planning, implementation and evaluation or control of during learning the covid 19 pandemic at SMP Negeri 7 Sijunjung. The results showed that, 1). The planning stage is carried out through several stages, namely the first small meeting of the Headmaster, Deputy of Headmaster for Curriculum sector and the Chief of Administration, the results of the small meeting are brought to the teachers council meeting, then the results of the meeting are socialized to parents and students 2). The implementation of daring learning the Covid 19 pandemic at SMP Negeri 7 Sijunjung was carried out by the Headmaster to each field teacher, namely by using the Whatsapp Group Mapel, Google Classrom and Google Form to send material, whether in the form of photos, videos or LKPD 3). Evaluation of daring learning the covid 19 pandemic at SMP Negeri 7 Sijunjung was carried out by the Headmaster along with the Deputy of Headmaster for Curriculum sector by controlling directly into the class and subject groups of each teacher and conducting monthly briefings related to daring learning.